ANALISIS KARAKTERISTIK POMPA SENTRIFUGAL DENGAN SISTEM SERI DAN PARALEL - Subagyo, Rachmat; -, Muchsin; Aulia, Rezky (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2013)
The pump is a device for providing mechanical energy to the fluid. At the pump, the fluid density is constant and large. The pump is intended for the transport fluid (horizontal and vertical), raising the pressure and increase speed. The main weakness of the centrifugal pump is located on the limitation of the pressure blower (delivery presure) and not able to provoke their own. For that use multi-level which is usually the same wheelbase and driven by the motor. Various circuits can be used to satisfy a certain condition. Namely series and parallel systems, where a parallel system to increase the pump head and the series system To increase the flow rate.To overcome these problems the research conducted on the characteristics of the pump between the pump with series and parallel systems. To find out the advantages of each characteristic. In this activity, carried out research using the dependent variable valve opening, the load and the volume of water comprising: valve openings ¼, ½, ¾ and 1 and for loading performed at a load 0.25 kg, 0.5 kg, 0.75 kg and 1kg and to use as much water 5 litre, while independent variables are used, namely engine speed of 2980 rpm most of the worth of the smallest worth up to 2945 rpm, the pressure at the pump in and out and the time spent to reach the volume of water by 5 litre. From the test results shows that the comparison between series and parallel pumps each have advantages, further increase in the pump head series and parallel pump further improve the discharge, the pump power and highest efficiency in parallel with 112.79 worth of watts and 65% and the power series highest pump valued at 113.00 watts and the highest efficiency of 53%.